2008
DOI: 10.1210/jc.2007-1618
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Visceral Fat Excess after Spontaneous Catch-Up Growth in Children with Low Birth Weight

Abstract: The amount of visceral fat is in post-catch-up SGA children excessive by the age of 6 yr. In populations at risk for type 2 diabetes or metabolic syndrome after fetal growth restraint, the time window for early intervention may have to be advanced into prepubertal childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 14 publications
9
60
0
3
Order By: Relevance
“…For example, there is specific gain of visceral adipose tissue by 6 years of age in children born after intrauterine growth retardation. 34 The prospective evidence is supported by studies reporting body composition at birth as determined by magnetic resonance imaging. These show that although smaller babies have reduced subcutaneous fat with the reduction proportionate to birth size, visceral fat is preserved so that the smaller babies have relative visceral adiposity.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 94%
See 1 more Smart Citation
“…For example, there is specific gain of visceral adipose tissue by 6 years of age in children born after intrauterine growth retardation. 34 The prospective evidence is supported by studies reporting body composition at birth as determined by magnetic resonance imaging. These show that although smaller babies have reduced subcutaneous fat with the reduction proportionate to birth size, visceral fat is preserved so that the smaller babies have relative visceral adiposity.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 94%
“…10 Further, so-called 'catch-up' or 'compensatory' growth, accelerated growth after early nutritional restriction, may pose particular problems for later metabolic health. The deleterious effects of catch-up growth are apparent from theoretical models, 109 animal studies, 110 clinical evidence 34,111 and epidemiological studies. 65,66 The relative contributions of impaired prenatal growth and accelerated postnatal growth in such situations remain to be disentangled, although some experimental studies 112 have suggested that attenuation of catch-up growth after low birth weight is protective against later obesity.…”
Section: Final Commentsmentioning
confidence: 99%
“…These findings seem to imply that regarding weight, LGA-born children grew too fast for their GA, which had already exposed them to an elevated risk for metabolic consequences such as metabolic syndrome. 14,15 From birth onward, LGA PTs were unsuccessful in maintaining their well-balanced body proportions as their weight gain exceeded their height gain. Consequently, by the age of 4 years they were comparable to LGA FTs.…”
Section: Discussionmentioning
confidence: 99%
“…Greater weight gains and relatively high BMIs imply that metabolic consequences such as metabolic syndrome are of specific concern. 14,15,21 In this study we assessed growth up to the age of 4 years, which is exactly the age span during which children are most likely to develop overweight and obesity that persists into adolescence. 22 It may be helpful to specifically use weight-forheight charts to distinguish between catch-up growth, which is expected to take place at least during infancy in PTborn children, 5,23 and excessive growth during which weight-for-height will increase and exceed the 50th percentile of the reference population.…”
Section: Discussionmentioning
confidence: 99%
“…. Também não se tem observado consenso dessa relação para os pré-escolares sendo descrita como positiva no estudo de VALŪNIENE et al 139 e como negativa no estudo de IBÁÑEZ et al 55,56 .…”
Section: Figuraunclassified